Common errors made in attempt to contract the pelvic floor muscles in women early after delivery: A prospective observational study. (January 2018) - Neels, Hedwig; De Wachter, Stefan; Wyndaele, Jean-Jacques; Van Aggelpoel, Tinne; Vermandel, Alexandra
Abstract: Objectives: The ability to perform a correct pelvic floor muscle contraction (PFMC) is necessary to start pelvic floor muscle training after delivery. COMMOV are "c "ontractions of "o "ther "m "uscles (m. rectus abdominus, the gluteal muscles, and the adductors), and other "mov "ements (pelvic tilt, breath holding, and straining) performed in addition to or instead of the PFMC. COMMOV are probably the most common errors in attempt to contract the pelvic floor muscles during the first days after delivery. The aims of this study were to observe the prevalence of COMMOV, to investigate whether COMMOV influence the ability to perform a PFMC, and whether verbal instructions are effective to unlearn the COMMOV postpartum. Study design: A Prospective Observational Study was performed in women during the first through sixth day postpartum. PFMC and COMMOV were evaluated with visual observation. Women who did not show correct isolated PFMC received verbal instructions and were re-evaluated. Interobserver variability and agreement were calculated. Chi-square, Kappa, Risk Ratio, and McNemar were used. Results: A total of 382 women participated, 2.36 (±1.2) days postpartum. Twohundred sixteen, 57%, CI (52–62%), showed COMMOV. The chance to perform a correct PFMC was 2.65 times higher without COMMOV (p = 0.0001). Verbal feedback was effective (57% reduced to 3%) to abandon COMMOV during PFMC. Conclusion: COMMOV are common errors performed during attempts to contract the pelvic floor muscles after delivery. They can reduce the ability to contract the pelvic floor muscles, but can easily been unlearned with visual observation and verbal feedback.